Sex hormone binding globulin (SHBG) as a predictor of liver fibrosis in subjects with nonalcoholic fatty liver disease (NAFLD) - Abeer Abdel-latif; Ula Mabid Al-Jarhi; Dina Hesham; Mona khozam; Shaimaa A. Fathy (SpringerOpen, 2023)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is the fastest growing cause of chronic liver disease worldwide. The prevalence of NAFLD increases in parallel with the increasing prevalence in obesity, metabolic syndrome and type 2 diabetes (T2DM). Recently, more evidence indicates the important role of sex hormone binding globulin (SHBG) on metabolic health. Methods A controlled cross-sectional cohort study was conducted upon 60 patients (NAFLD and control group). Patients were categorized according to the NAFLD fibrosis score. All patients subjected to routine labs and SHBG measurement. Results BMI was 35.80 ± 6.56 SD and 23.23 ± 2.5 SD in the NAFLD group and control group respectively. The NAFLD fibrosis score was 2.12 ± 1.47 SD. Fifty patients were categorized as advanced liver fibrosis: F3-F4 (> 0.675). No patients scored to exclude advanced liver fibrosis: F0-F2 (< − 1.455). The remaining 10 patients were categorized as indeterminate (in-between). There was a significant correlation between age, mid-arm circumference, waist circumference, BMI, serum albumin level, lipid profile components, as well as the NAFLD fibrosis score and SHBG levels using univariable regression analysis. There was also a significant correlation between mid-arm circumference, waist circumference, lipid profile components as well as SHBG levels and the NAFLD fibrosis score using univariable regression analysis. SHBG can predict severe liver fibrosis (F3-F4) in our NAFLD female cohort at a cut-off level of > 10 ng/mL, with 34% sensitivity and 90% specificity, area under the ROC curve (AUC) = 0.548, with 95% Confidence interval 0.414 to 0.677. Conclusion SHBG is positively correlated to severe fibrosis in female NAFLD patients. It is an efficient positive predictor of severe fibrosis in female NAFLD patients at a cut-off level > 10 ng/ml, with a high specificity and modest sensitivity.